Analisis Manajemen Risiko Pada UMKM Baso Urat Cici - Ramadhan, Fadlillah (Jurnal Serambi Ekonomi dan Bisnis, 2024)
Small and Medium Enterprises (SMEs) play a vital role in the national economy but often face various risks threatening their sustainability. This study analyzes risk management in Baso Urat Cici SMEs, focusing on five main dimensions: financial, human resources (HR), product, marketing, and operational risks. A qualitative approach was applied through in-depth interviews and SWOT analysis. The findings reveal financial risks in unstable cash flow and limited access to capital. HR risks include low employee skills and high turnover. Product risks involve raw material quality and taste consistency, which may affect reputation. Marketing risks stem from intense competition and demand fluctuations, while operational risks relate to inefficiencies in production and distribution. The SWOT analysis highlights product innovation and customer loyalty as strengths. Weaknesses include suboptimal financial management and limited HR capacity. Opportunities arise from a vast market and the trend of ready-to-eat food consumption, while threats include increasing competition and economic uncertainty. It is recommended that Baso Urat Cici adopt product diversification, stricter financial management, and employee training to enhance competitiveness.